The practice of capital structure choice in the Czech Republic: A comparative study based on the global data - Lenka Strýčková (Journal of International Studies)
The aim of this contribution is to reveal the general practice in corporate financing in the Czech Republic, capital structure choice in particular, by means of comparison with the global data. The comparative study is based on primary data from the Czech Republic obtained via a questionnaire survey, and comparison with the data from various countries in Europe and America published in empirical surveys since 2001. The crux of this comparison is the use of the same questions that were used by Graham and Harvey for the first time in 2001. Unlike the original study, which examined several aspects of corporate finance in a single country, this study is focused on the cross-country comparisons of views on determinants of capital structure. The study revealed both differences and similarities between Czech, American and European companies. As the most important factor affecting the choice of the appropriate amount of debt for Czech respondents was “Financial flexibility”, likewise in the other countries. Surprisingly, the tax advantages are not considered to be of a high importance to Czech firms and a striking proportion of respondents have no target debt ratio; such results weren’t found by any previous study.